Polyolefin conductive thin film prepared by flash evaporation method and preparation method and application of polyolefin conductive thin film

By adding evenly dispersed carbon nanotubes to the film and using flash evaporation to prepare polyolefin conductive films, the problem of hydrophobic layer failure and high cost of carbon paper in an electric field environment is solved, and the comprehensive improvement of conductivity uniformity, breathability and hydrophobicity is achieved. It is suitable for the membrane electrode gas diffusion layer.

CN119505401APending Publication Date: 2025-02-25XIAMEN DANGSHENG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411662754.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing carbon paper used for the acidic membrane electrode gas diffusion layer is prone to hydrophobic layer damage in an electric field environment and is costly.

Method used

By adding evenly dispersed carbon nanotubes to the film, a polyolefin conductive film was prepared by flash evaporation. The film had excellent electrical conductivity and uniform conductivity, with hydrophobic and high breathability, and could replace carbon paper.

Benefits of technology

The comprehensive improvement of conductive uniformity, breathability and hydrophobicity is achieved, and the cost is reduced, and it is suitable for the application of membrane electrode gas diffusion layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143862020000081
    Figure BDA0005143862020000081
  • Figure BDA0005143862020000171
    Figure BDA0005143862020000171
  • Figure BDA0005143862020000181
    Figure BDA0005143862020000181
Patent Text Reader

Abstract

The invention discloses a flash evaporation polyolefin conductive film as well as a preparation method and application thereof, and relates to the technical field of flash evaporation breathable films. The preparation method comprises the following steps: calcining a carbon nanotube, modifying with hexadecyl trimethyl ammonium bromide, preparing conductive master batches from the polymer melt A, a coupling agent and the modified carbon nanotube, and preparing the thin film from a spinning solution containing the polymer melt B, the conductive master batches and a spinning solvent through flash spinning equipment. According to the preparation method, the carbon nanotubes can efficiently adsorb hexadecyl trimethyl ammonium bromide to form a molecular wrapping layer, so that uniform dispersion of the carbon nanotubes in a spinning solution is promoted, the conductivity uniformity of the prepared thin film is guaranteed, the carbon nanotubes are of a curled round tube morphology structure, the porosity of the thin film is improved due to dispersion of the carbon nanotubes in the thin film, and the conductivity of the thin film is improved. The air permeability of the film can be highly maintained, and the prepared film is high in conductivity and hydrophobicity, can replace carbon paper to prepare a film electrode gas diffusion layer, and is low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flash vaporization breathable films, and in particular to a flash vaporization polyolefin conductive film and a preparation method and application thereof. Background Art

[0002] Electrocatalytic CO2 reduction technology is a technology with great industrial potential. It converts CO2 into carbon-based fuels such as carbon monoxide (CO), formic acid, ethanol, ethylene, and acetic acid, which can reduce people's dependence on fossil fuels. In recent years, researchers have developed a series of electrocatalysts with excellent performance to improve the selectivity and stability of various products. At the same time, they have also innovated and improved the design of electrolytic cells. Among them, membrane electrode electrocatalysis of CO2 is a method with good prospects. At present, the acidic membrane electrode gas diffusion layer (GDE) used in research work mostly uses carbon paper, which is a composite material made of carbon fiber as raw material. Carbon paper is light in weight, smooth in surface, corrosion-resistant, uniform in porosity and high in conductivity, making it widely used in fuel cells, lithium batteries, electrocatalysis and other fields. It is usually made of chopped carbon fiber and has a fiber porous structure, which can establish an effective channel for the conduction of gas and water.

[0003] However, when using carbon paper as the gas diffusion layer of the acidic membrane electrode, the carbon paper needs to be modified with polytetrafluoroethylene to have good hydrophobicity. In an electric field environment, the hydrophobic layer will usually be destroyed within a certain period of time (ranging from 10 to 1000 hours). In addition, the price of carbon paper modified with polytetrafluoroethylene is expensive. At present, the average price of carbon paper used in most university laboratories is about 350 yuan per sheet, resulting in high costs. Summary of the invention

[0004] The present invention provides a flash-evaporated polyolefin conductive film and a preparation method and application thereof. By adding evenly dispersed carbon nanotubes into the film, the film has excellent conductive function and uniform conductivity, and at the same time has hydrophobicity and high air permeability. It can replace carbon paper to prepare a membrane electrode gas diffusion layer and has a relatively low price.

[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a conductive masterbatch, comprising the following steps:

[0006] The carbon nanotubes are calcined in an inert gas atmosphere at a temperature greater than or equal to 600° C. and less than or equal to 900° C., and then added into an organic solvent containing hexadecyltrimethylammonium bromide to obtain a mixed solution, heated and stirred, filtered, and dried to obtain modified carbon nanotubes.

[0007] 62wt%-73wt% polymer melt A, 1-3wt%wt% coupling agent, and 25wt%-35wt%wt% modified carbon nanotubes are mixed, and then added into a twin-screw extruder for melt extrusion granulation to obtain a conductive masterbatch.

[0008] By adopting the above scheme, since carbon nanotubes are not easy to disperse in polar solvents and have the characteristics of agglomeration, the present application uses hexadecyl trimethyl ammonium bromide to modify the carbon nanotubes, and the carbon nanotubes can adsorb hexadecyl trimethyl ammonium bromide to form a molecular wrapping layer, and the groups carried by hexadecyl trimethyl ammonium bromide are used to produce electrostatic repulsion and steric hindrance effects, thereby promoting the carbon nanotubes to be uniformly dispersed in the subsequent spinning solution with more polar solvents, and the carbon nanotube particles are not easy to agglomerate, ensuring the conductive uniformity of the prepared film. At the same time, the carbon nanotubes are pre-treated with high-temperature calcination, which helps to change their surface properties during the high-temperature calcination process, so that the carbon nanotubes have more microholes and pores. When the carbon nanotubes are subsequently treated with hexadecyl trimethyl ammonium bromide, the adsorption efficiency of the carbon nanotubes on hexadecyl trimethyl ammonium bromide can be improved, and the dispersion uniformity of the carbon nanotubes in the spinning solution can be further improved.

[0009] As a preferred embodiment, the mass ratio of hexadecyltrimethylammonium bromide to carbon nanotubes in the mixed solution is greater than or equal to 2 and less than or equal to 4, and the mass fraction of hexadecyltrimethylammonium bromide in the organic solvent containing hexadecyltrimethylammonium bromide is greater than or equal to 30wt% and less than or equal to 40wt%.

[0010] By adopting the above scheme, the present application controls the ratio of hexadecyltrimethylammonium bromide and carbon nanotubes during the surface modification process, ensuring that more hexadecyltrimethylammonium bromide can fully cover the surface of the carbon nanotubes to form a molecular wrapping layer, thereby promoting the uniformity of dispersion of the carbon nanotubes in the spinning solution.

[0011] As a preferred embodiment, the calcination time of the carbon nanotubes is greater than or equal to 1 hour and less than or equal to 5 hours.

[0012] As a preferred embodiment, the heating temperature of the mixed solution is greater than or equal to 50°C and less than or equal to 80°C.

[0013] As a preferred solution, the temperature of the twin-screw extruder is set to be greater than or equal to 160°C and less than or equal to 210°C.

[0014] As a preferred embodiment, the polymer melt A is at least one of polyesters such as polyethylene, high-density polyethylene, polypropylene, polybutene, polymethylpentene, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, PET, and polylactic acid.

[0015] As a preferred embodiment, the coupling agent is at least one of a silane coupling agent, a titanate coupling agent, and a phosphate coupling agent.

[0016] As a preferred solution, the length of the carbon nanotube is greater than or equal to 1 μm and less than or equal to 50 μm, and the diameter is greater than or equal to 5 nm and less than or equal to 100 nm.

[0017] By adopting the above scheme, the larger the size of the carbon nanotubes, the lower the air permeability of the subsequently prepared film will be as the size increases, and the dispersion uniformity of the carbon nanotubes in the film will also decrease. The smaller the size of the carbon nanotubes, the better the conductivity uniformity of the film.

[0018] As a preferred embodiment, the inert gas is nitrogen or argon.

[0019] As a preferred embodiment, the organic solvent is at least one of methanol, ethanol, propanol, ethyl acetate, n-hexane, petroleum ether, xylene, tetrahydrofuran, dichloromethane and trichloroethylene.

[0020] As a preferred embodiment, the drying temperature is greater than or equal to 60°C and less than or equal to 80°C.

[0021] In order to solve the above technical problems, a second object of the present invention is to provide a conductive masterbatch.

[0022] In order to solve the above technical problems, the third object of the present invention provides a method for preparing a polyolefin conductive film by a flash evaporation method, comprising the following steps:

[0023] The polymer melt B, the conductive masterbatch and the spinning solvent are mixed in a reaction kettle, heated to a temperature greater than or equal to 190° C. and less than or equal to 230° C., pressurized to a temperature greater than or equal to 10 MPa and less than or equal to 12 MPa, and stirred in a closed manner until the temperature and pressure are stable to obtain a spinning solution, wherein the spinning solution includes 8wt%-13wt% of the polymer melt, 7wt%-10wt% of the conductive masterbatch and 77wt%-85wt% of the spinning solvent by mass fraction,

[0024] The spinning solution is ejected through the spinneret holes of the connected flash spinning equipment, stretched and opened by an air amplifier to form an ultrafine fiber web, which is then laid on a mobile device and subjected to cold pressing and hot rolling to obtain a film.

[0025] By adopting the above scheme, the present application adopts a conductive masterbatch containing carbon nanotubes to prepare a film. The carbon nanotubes present a curled circular tube morphology. The dispersion of the carbon nanotubes in the film helps to improve the porosity of the film, so that the air permeability of the film is maintained at a high level. The conductivity and hydrophobicity of the prepared film are both high, which can meet the requirements of application in the gas diffusion layer of the membrane electrode acidic membrane electrode. The present application pre-prepare the carbon nanotubes with high-density polyethylene to prepare a conductive masterbatch, so that the carbon nanotubes are pre-dispersed in the polymer system, which helps to improve the subsequent dispersion uniformity of the carbon nanotubes in the spinning solution, so that the conductive uniformity, tensile strength and air permeability of the film are comprehensively improved.

[0026] As a preferred embodiment, the polymer melt B is at least one of polyesters such as polyethylene, high-density polyethylene, polypropylene, polybutene, polymethylpentene, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, PET, and polylactic acid.

[0027] As a preferred embodiment, the spinning solvent is at least one of toluene, benzene, n-hexane, butane, pentene, heptane, octane, cyclohexane, cyclopentane, dichloromethane, carbon tetrachloride, chloroform, chloromethane, ethyl chloride, dichloroethylene, trichlorofluoromethane, dichlorotrifluoroethane, pentafluoropropane, heptafluoropropane, perfluorohexane, perfluorohexane, perfluoroheptane, octafluorocyclopentane, and alcohol solvents.

[0028] As a preferred solution, the spinning solvent is 50wt%-60wt% of n-hexane and 20wt%-30wt% of cyclopentane in the spinning solution.

[0029] As a preferred embodiment, the spinning solution is stirred in the reactor in a closed manner for a period of time greater than or equal to 2 hours and less than or equal to 5 hours.

[0030] As a preferred solution, the air flow velocity of the spinneret of the flash spinning equipment is greater than or equal to 10000 m / min and less than or equal to 13000 m / min.

[0031] As a preferred solution, the diameter of the spinneret hole is greater than or equal to 1 μm and less than or equal to 5 μm.

[0032] As a preferred solution, the cold pressing pressure is greater than or equal to 0.5 MPa and less than or equal to 2 MPa.

[0033] As a preferred embodiment, the hot rolling temperature is greater than or equal to 120° C. and less than or equal to 140° C., and the pressure is greater than or equal to 3 MPa and less than or equal to 4 MPa.

[0034] In order to solve the above technical problems, a fourth object of the present invention is to provide a flash evaporated polyolefin conductive film.

[0035] In order to solve the above technical problems, the fifth object of the present invention provides an application of a flash evaporated polyolefin conductive film in the field of preparing conductive materials or membrane electrode gas diffusion layers.

[0036] As a preferred solution, the membrane electrode comprises a proton exchange membrane, a catalytic layer and a gas diffusion layer which are compounded in sequence, and the gas diffusion layer is a polyolefin flash vaporization gas permeable membrane.

[0037] As a preferred embodiment, the method for preparing a membrane electrode includes the following steps: applying a catalyst layer slurry on one side of a proton exchange membrane by slit coating to form an anode catalyst layer or a cathode catalyst layer, and combining a gas diffusion layer on the side of the proton exchange membrane coated with the catalyst layer to prepare a membrane electrode.

[0038] As a preferred solution, the material of the proton exchange membrane is at least one of perfluorosulfonic acid resin, polyvinylidene fluoride resin, polyaryletherketone resin and polyacrylamide resin.

[0039] The present application adopts flash evaporation technology to prepare conductive film, and improves the conductivity by adding carbon nanotubes with excellent conductive properties. Since the dispersion of carbon nanotubes in the spinning solution is limited, the carbon nanotube particles are easy to agglomerate, resulting in uneven conductivity of the prepared film, and the air permeability and tensile strength of the film are both reduced to a certain extent. The present application uses hexadecyltrimethylammonium bromide to modify the carbon nanotubes. The carbon nanotubes can adsorb hexadecyltrimethylammonium bromide to form a molecular wrapping layer, and the groups carried by hexadecyltrimethylammonium bromide are used to produce electrostatic repulsion and steric hindrance effects, thereby promoting the dispersion uniformity of the carbon nanotubes in the spinning solution. While ensuring the mechanical strength of the film, the conductive uniformity and air permeability of the film are improved. When applied to the preparation of the gas diffusion layer of the acidic membrane electrode, the gas diffusion layer made of the film is used as a part of the membrane electrode and assembled with other components into a complete electrochemical reaction system. The uniform conductivity of the film will not affect the uniform distribution of the current, avoid excessive local current density to increase polarization, and improve the output power and efficiency of the battery.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. In the present application, carbon nanotubes are subjected to high-temperature calcination treatment in advance so that the carbon nanotubes produce more microholes and pores, and are modified by using hexadecyltrimethylammonium bromide. The carbon nanotubes can efficiently adsorb hexadecyltrimethylammonium bromide to form a molecular wrapping layer, and the groups carried by hexadecyltrimethylammonium bromide are used to produce electrostatic repulsion and steric hindrance effects, thereby promoting the uniform dispersion of the carbon nanotubes in the subsequent spinning solution with a large amount of polar solvents, thereby ensuring the conductive uniformity of the prepared film.

[0042] 2. The present application adopts a conductive masterbatch containing carbon nanotubes to prepare a film. The carbon nanotubes are pre-mixed with high-density polyethylene to prepare a conductive masterbatch so that the carbon nanotubes are pre-dispersed in the polymer system, which helps to improve the uniformity of the subsequent dispersion of the carbon nanotubes in the spinning solution. The carbon nanotubes present a curled circular tube morphology. The dispersion of the carbon nanotubes in the film helps to improve the porosity of the film, so that the air permeability of the film is maintained at a high level. The conductivity and hydrophobicity of the prepared film are both high, which can meet the requirements of application in the gas diffusion layer of the acidic membrane electrode. DETAILED DESCRIPTION

[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The following Table 1 shows the sources and types of raw materials used in the examples and comparative examples of the present application. Unless otherwise specified, the raw materials used can be obtained commercially, and the same raw materials are used in parallel experiments.

[0045] Table 1 - Sources of raw materials used in the examples and comparative examples of the present application

[0046]

[0047] Example 1

[0048] A method for preparing a polyolefin conductive film by a flash evaporation method comprises the following steps:

[0049] (1) Preparation of modified carbon nanotubes: carbon nanotubes with a diameter of 10-15 nm and a length of 3-12 μm were calcined in a nitrogen atmosphere at 800° C. for 2 h. The calcined carbon nanotubes were then added to ethanol containing 40 wt % hexadecyltrimethylammonium bromide, wherein the mass ratio of the carbon nanotubes to the hexadecyltrimethylammonium bromide in the mixed solution was 1:3. The mixture was heated to 60° C. and stirred for 30 min. The mixture was then filtered and dried at 80° C. to obtain modified carbon nanotubes.

[0050] (2) Prepare conductive masterbatch: 67 wt% high-density polyethylene, 3 wt% KH550 silane coupling agent, and 30 wt% modified carbon nanotubes are mixed by a blending device, and then added into a twin-screw extruder for melt extrusion granulation. The temperature of the twin-screw extruder is set at 160°C-210°C to obtain conductive masterbatch.

[0051] (3) Prepare spinning solution, deliver 12 wt% of high-density polyethylene and 8 wt% of conductive masterbatch accounting for 12 wt% of the spinning solution to a pretreatment tank to form a uniform polymer mixture, deliver 50 wt% of n-hexane and 30 wt% of cyclopentane accounting for 50 wt% of the spinning solution to another pretreatment tank to obtain a uniform solvent mixture, mix the polymer mixture and the solvent mixture in a reactor, preheat to 180°C, then introduce nitrogen and pressurize to 11 MPa, finally heat to 220°C, stir in a closed container for 2 hours, and obtain the spinning solution after the temperature and pressure are stabilized.

[0052] (4) Prepare a flash-spun polyolefin conductive film, transfer the spinning solution to the nozzle of a connected flash spinning device for spinning, vaporize the solvent in a room temperature and pressure environment, and the polymer is pulled by steam to form an ultrafine fiber bundle. The ejection air flow rate is 12000 m / min, and the spinneret aperture is 2 μm. The ultrafine fiber bundle is guided to an air amplifier through a steering device. The air flow speed of the air amplifier is 12000 m / min. The ultrafine fiber web is formed by high-pressure air stretching and laid on a moving mesh curtain. The mesh is then cold-pressed at a pressure of 1 MPa and hot-rolled at 130°C and 3.5 MPa to obtain a film with a thickness of about 0.15 mm.

[0053] Example 2

[0054] A method for preparing a polyolefin conductive film by a flash evaporation method comprises the following steps:

[0055] (1) Preparation of modified carbon nanotubes: carbon nanotubes with a diameter of 10-15 nm and a length of 3-12 μm were calcined in a nitrogen atmosphere at 700° C. for 3 h. The calcined carbon nanotubes were then added to ethanol containing 30 wt % hexadecyltrimethylammonium bromide, wherein the mass ratio of the carbon nanotubes to hexadecyltrimethylammonium bromide in the mixed solution was 1:4. The mixture was heated to 60° C. and stirred for 30 min. The mixture was then filtered and dried at 80° C. to obtain modified carbon nanotubes.

[0056] (2) Prepare conductive masterbatch: 73 wt% high-density polyethylene, 2 wt% KH550 silane coupling agent, and 25 wt% modified carbon nanotubes by using a blending device, and add them into a twin-screw extruder for melt extrusion granulation. The temperature of the twin-screw extruder is set at 160°C-210°C to obtain conductive masterbatch.

[0057] (3) Prepare spinning solution, deliver 10 wt% of high-density polyethylene and 10 wt% of conductive masterbatch accounting for 10 wt% of the spinning solution to a pretreatment tank to form a uniform polymer mixture, deliver 55 wt% of n-hexane and 25 wt% of cyclopentane accounting for 55 wt% of the spinning solution to another pretreatment tank to obtain a uniform solvent mixture, mix the polymer mixture and the solvent mixture in a reactor, preheat to 180°C, then introduce nitrogen and pressurize to 11 MPa, finally heat to 220°C, stir in a closed manner for 2 hours, and obtain the spinning solution after the temperature and pressure are stabilized.

[0058] (4) Prepare a flash-spun polyolefin conductive film, transfer the spinning solution to the nozzle of a connected flash spinning device for spinning, vaporize the solvent in a room temperature and pressure environment, and the polymer is pulled by steam to form an ultrafine fiber bundle. The ejection air flow rate is 12000 m / min, and the spinneret aperture is 2 μm. The ultrafine fiber bundle is guided to an air amplifier through a steering device. The air flow speed of the air amplifier is 12000 m / min. The ultrafine fiber web is formed by high-pressure air stretching and laid on a moving mesh curtain. The mesh is then cold-pressed at a pressure of 1 MPa and hot-rolled at 130°C and 3.5 MPa to obtain a film with a thickness of about 0.15 mm.

[0059] Example 3

[0060] A method for preparing a polyolefin conductive film by a flash evaporation method comprises the following steps:

[0061] (1) Preparation of modified carbon nanotubes: carbon nanotubes with a diameter of 10-15 nm and a length of 3-12 μm were calcined in a nitrogen atmosphere at 600° C. for 4 h. The calcined carbon nanotubes were then added to ethanol containing 35 wt % hexadecyltrimethylammonium bromide, wherein the mass ratio of the carbon nanotubes to the hexadecyltrimethylammonium bromide in the mixed solution was 1:3. The mixture was heated to 60° C. and stirred for 20 min. The mixture was then filtered and dried at 80° C. to obtain modified carbon nanotubes.

[0062] (2) Prepare conductive masterbatch: 62 wt% high-density polyethylene, 3 wt% KH550 silane coupling agent, and 35 wt% modified carbon nanotubes are mixed by a blending device, and then added into a twin-screw extruder for melt extrusion granulation. The temperature of the twin-screw extruder is set at 160°C-210°C to obtain conductive masterbatch.

[0063] (3) Prepare spinning solution, deliver 11wt% of high-density polyethylene and 9wt% of conductive masterbatch accounting for 11wt% of the spinning solution to a pretreatment tank to form a uniform polymer mixture, deliver 50wt% of n-hexane and 30wt% of cyclopentane accounting for 50wt% of the spinning solution to another pretreatment tank to obtain a uniform solvent mixture, mix the polymer mixture and the solvent mixture in a reactor, preheat to 180°C, then introduce nitrogen and pressurize to 11MPa, finally heat to 220°C, stir in a closed manner for 2h, and obtain the spinning solution after the temperature and pressure are stabilized.

[0064] (4) Prepare a flash-spun polyolefin conductive film, transfer the spinning solution to the nozzle of a connected flash spinning device for spinning, vaporize the solvent in a room temperature and pressure environment, and the polymer is pulled by steam to form an ultrafine fiber bundle. The ejection air flow rate is 12000 m / min, and the spinneret aperture is 2 μm. The ultrafine fiber bundle is guided to an air amplifier through a steering device. The air flow speed of the air amplifier is 12000 m / min. The ultrafine fiber web is formed by high-pressure air stretching and laid on a moving mesh curtain. The mesh is then cold-pressed at a pressure of 1 MPa and hot-rolled at 130°C and 3.5 MPa to obtain a film with a thickness of about 0.15 mm.

[0065] Example 4

[0066] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), modified carbon nanotubes are prepared by adding carbon nanotubes into ethanol containing 40wt% of hexadecyltrimethylammonium bromide, wherein the mass ratio of carbon nanotubes to hexadecyltrimethylammonium bromide in the mixed solution is 1:3, heating to 60°C and stirring for 30 minutes, followed by filtering and drying at 80°C to obtain modified carbon nanotubes.

[0067] Example 5

[0068] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), modified carbon nanotubes are prepared, carbon nanotubes with a diameter of 10-20 nm and a length of 5-15 μm are calcined in a nitrogen atmosphere at a temperature of 800° C. for 2 hours, and then the calcined carbon nanotubes are added to ethanol containing 40 wt% of hexadecyltrimethylammonium bromide, wherein the mass ratio of the carbon nanotubes to the hexadecyltrimethylammonium bromide in the mixed solution is 1:3, and the mixture is heated to 60° C. and stirred for 30 minutes, and then filtered and dried at 80° C. to obtain modified carbon nanotubes.

[0069] Example 6

[0070] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), modified carbon nanotubes are prepared, carbon nanotubes with a diameter of 8-15 nm and a length of 20-40 μm are calcined in a nitrogen atmosphere at a temperature of 800° C. for 2 hours, and then the calcined carbon nanotubes are added to ethanol containing 40 wt% of hexadecyltrimethylammonium bromide, wherein the mass ratio of the carbon nanotubes to the hexadecyltrimethylammonium bromide in the mixed solution is 1:3, and the mixture is heated to 60° C. and stirred for 30 minutes, and then filtered and dried at 80° C. to obtain modified carbon nanotubes.

[0071] Example 7

[0072] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), modified carbon nanotubes are prepared, carbon nanotubes with a diameter of 10-15 nm and a length of 3-12 μm are calcined in a nitrogen atmosphere at a temperature of 800° C. for 2 hours, and then the calcined carbon nanotubes are added to ethanol containing 40 wt% of hexadecyltrimethylammonium bromide, wherein the mass ratio of the carbon nanotubes to the hexadecyltrimethylammonium bromide in the mixed solution is 1:2, and the mixture is heated to 60° C. and stirred for 30 minutes, and then filtered and dried at 80° C. to obtain modified carbon nanotubes.

[0073] Example 8

[0074] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (3), a spinning solution is prepared, high-density polyethylene accounting for 13wt% of the spinning solution and 7wt% of conductive masterbatch are transported to a pretreatment tank to form a uniform polymer mixture, n-hexane accounting for 50wt% of the spinning solution and 30wt% of cyclopentane are transported to another pretreatment tank to obtain a uniform solvent mixture, the polymer mixture and the solvent mixture are mixed in a reactor, preheated to 180°C, then nitrogen is introduced and pressurized to 11MPa, and finally heated to 220°C, stirred in a closed manner for 2h, and after the temperature and pressure are stabilized, a spinning solution is obtained.

[0075] Comparative Example 1

[0076] A method for preparing a polyolefin conductive film by a flash evaporation process, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (2), a conductive masterbatch is prepared by mixing 67wt% of high-density polyethylene, 3wt% of KH550 silane coupling agent and 30wt% of carbon nanotubes with a diameter of 10-15nm and a length of 3-12μm using a blending device, and then adding the mixture into a twin-screw extruder for melt extrusion granulation, wherein the temperature of the twin-screw extruder is set at 160°C-210°C to obtain the conductive masterbatch.

[0077] Comparative Example 2

[0078] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), modified carbon nanotubes are prepared, and carbon nanotubes with a diameter of 10-15 nm and a length of 3-12 μm are calcined in a nitrogen atmosphere at a temperature of 800° C. for a calcination time of 2 h to obtain modified carbon nanotubes.

[0079] Comparative Example 3

[0080] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), modified graphene is prepared, graphene with an average thickness of 3.4-8nm and a diameter of 5-50μm is calcined in a nitrogen atmosphere at a temperature of 800°C for 2h, and then the calcined graphene is added to ethanol containing 40wt% of hexadecyltrimethylammonium bromide, wherein the mass ratio of graphene to hexadecyltrimethylammonium bromide in the mixed solution is 1:3, and the mixture is heated to 60°C and stirred for 30min, and then filtered and dried at 80°C to obtain the modified graphene.

[0081] In step (2), a conductive masterbatch is prepared by mixing 67 wt% high-density polyethylene, 3 wt% KH550 silane coupling agent, and 30 wt% modified graphene using a blending device, and then adding the mixture into a twin-screw extruder for melt extrusion granulation. The temperature of the twin-screw extruder is set at 160° C.-210° C. to obtain a conductive masterbatch.

[0082] Comparative Example 4

[0083] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), modified carbon black is prepared, carbon black with an average thickness of 3.4-8 nm and a diameter of 5-50 μm is calcined in a nitrogen atmosphere at a temperature of 800° C. for 2 hours, and then the calcined carbon black is added to ethanol containing 40 wt% of hexadecyltrimethylammonium bromide, wherein the mass ratio of carbon black to hexadecyltrimethylammonium bromide in the mixed solution is 1:3, and the mixture is heated to 60° C. and stirred for 30 minutes, and then filtered and dried at 80° C. to obtain modified carbon black.

[0084] In step (2), a conductive masterbatch is prepared by mixing 67 wt% high-density polyethylene, 3 wt% KH550 silane coupling agent, and 30 wt% modified carbon black using a blending device, and then adding the mixture into a twin-screw extruder for melt extrusion granulation. The temperature of the twin-screw extruder is set at 160° C.-210° C. to obtain a conductive masterbatch.

[0085] Comparative Example 5

[0086] A method for preparing a polyolefin conductive film by a flash evaporation method, wherein the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (3), a spinning solution is prepared, high-density polyethylene accounting for 15wt% of the spinning solution and 5wt% of conductive masterbatch are transported to a pretreatment tank to form a uniform polymer mixture, n-hexane accounting for 50wt% of the spinning solution and 30wt% of cyclopentane are transported to another pretreatment tank to obtain a uniform solvent mixture, the polymer mixture and the solvent mixture are mixed in a reactor, preheated to 180°C, then nitrogen is introduced and pressurized to 11MPa, and finally heated to 220°C, stirred in a closed manner for 2h, and after the temperature and pressure are stabilized, a spinning solution is obtained.

[0087] Comparative Example 6

[0088] A method for preparing a polyolefin conductive film by a flash evaporation method comprises the following steps:

[0089] (1) Preparation of modified carbon nanotubes: carbon nanotubes with a diameter of 10-15 nm and a length of 3-12 μm were calcined in a nitrogen atmosphere at 800° C. for 2 h. The calcined carbon nanotubes were then added to ethanol containing 40 wt % hexadecyltrimethylammonium bromide, wherein the mass ratio of the carbon nanotubes to the hexadecyltrimethylammonium bromide in the mixed solution was 1:3. The mixture was heated to 60° C. and stirred for 30 min. The mixture was then filtered and dried at 80° C. to obtain modified carbon nanotubes.

[0090] (2) Prepare spinning solution, deliver 17.6wt% of high-density polyethylene and 2.4wt% of modified carbon nanotubes, which account for 17.6wt% of the spinning solution, to a pretreatment tank to form a uniform polymer mixture, deliver 50wt% of n-hexane and 30wt% of cyclopentane, which account for 50wt% of the spinning solution, to another pretreatment tank to obtain a uniform solvent mixture, mix the polymer mixture and the solvent mixture in a reactor, preheat to 180°C, then introduce nitrogen and pressurize to 11MPa, finally heat to 220°C, and stir in a closed environment for 2h. After the temperature and pressure are stabilized, the spinning solution is obtained.

[0091] (3) Prepare a flash-spun polyolefin conductive film, transfer the spinning solution to the nozzle of a connected flash spinning device for spinning, vaporize the solvent in a room temperature and pressure environment, and the polymer is pulled by steam to form an ultrafine fiber bundle. The ejection air flow rate is 12000 m / min, and the spinneret aperture is 2 μm. The ultrafine fiber bundle is guided to an air amplifier through a steering device. The air flow speed of the air amplifier is 12000 m / min. The ultrafine fiber web is formed by high-pressure air stretching and laid on a moving mesh curtain. The mesh is then cold-pressed at a pressure of 1 MPa and hot-rolled at 130°C and 3.5 MPa to obtain a film with a thickness of about 0.15 mm.

[0092] Performance testing

[0093] 1. Air permeability: The films of the examples and comparative examples were tested for air permeability according to GB / T 5453 standard, with a test area of ​​20 cm 2 , pressure difference 200Pa, the test results are shown in Table 2 below.

[0094] 2. Hydrophobicity: The surface contact angle test of the films of the embodiments and comparative examples was performed according to the GB / T 30693-2014 standard. Water drops were dropped on the film surface and the contact angle formed by the water drops on the film surface was measured. The test results are shown in Table 2 below.

[0095] 3. Conductivity: Four film samples of the same size were cut from different parts of the films of the embodiment and the comparative example as a group of parallel test samples. The conductivity of the film samples of the embodiment and the comparative example was tested according to the test method of ion conductivity of power battery film of NB / T 10827-2021. The unit is S / m. The test results are shown in Table 2 below.

[0096] 4. Tensile strength: The tensile strength of the films of the embodiments and comparative examples was tested according to GB / T12914 standard. The test results are shown in Table 2 below.

[0097] Table 2 - Performance test results of the films of the present application examples and comparative examples

[0098]

[0099]

[0100] As shown in Table 2, by comparing the schemes of Example 1 and Comparative Examples 1-2, it can be seen that in Comparative Examples 1-2, uncalcined or calcined carbon nanotubes are directly mixed with high-density polyethylene to make conductive masterbatches, and the film is prepared by flash evaporation technology. The carbon nanotubes have limited dispersibility in the spinning solution, which leads to easy agglomeration of carbon nanotube particles, resulting in uneven conductivity of the prepared film, and the air permeability and tensile strength of the film are both reduced to a certain extent. When used to prepare the gas diffusion layer of the acidic membrane electrode, the uneven conductivity of the film will affect the uniform distribution of the current, resulting in excessive local current density, thereby increasing polarization and reducing the output power and efficiency of the battery. Unlike Comparative Examples 1-2, Example 1 of the present application uses hexadecyltrimethylammonium bromide to modify the carbon nanotubes. The carbon nanotubes can adsorb hexadecyltrimethylammonium bromide to form a molecular wrapping layer, and the groups carried by hexadecyltrimethylammonium bromide are used to produce electrostatic repulsion and steric hindrance effects, thereby promoting the uniformity of the dispersion of the carbon nanotubes in the spinning solution and improving the uniformity of the conductivity of the film.

[0101] As shown in Table 2, by comparing the schemes of Example 1 and Comparative Examples 3-4, it can be seen that Example 1 of the present application uses carbon nanotubes as conductive fillers to prepare the film. The carbon nanotubes have a curled circular tube morphology. Their dispersion in the film helps to improve the porosity of the film, so that the air permeability of the film is maintained at a high level, and the conductivity and hydrophobicity of the prepared film are both high, which can meet the requirements of application in the gas diffusion layer of the acidic membrane electrode; Comparative Example 3 uses graphene as a conductive filler to prepare the film. Since graphene has a planar structure showing a honeycomb lattice, when it is dispersed in a polyethylene film, the pores will become smaller or even reduced, resulting in a significant decrease in permeability, and the conductivity and hydrophobicity of the film prepared by graphene are reduced, and the overall performance is poor; Comparative Example 4 uses carbon black as a conductive filler to prepare the film. Since the particles of carbon black are generally amorphous spherical, the prepared film is relatively dense, the porosity is reduced, the air permeability of the film is insufficient, and the conductivity and hydrophobicity are both reduced.

[0102] As shown in Table 2, by comparing the solutions of Example 1 and Comparative Example 6, it can be seen that compared with Comparative Example 6, the present application pre-disperses the carbon nanotubes with high-density polyethylene to prepare a conductive masterbatch, so that the carbon nanotubes are pre-dispersed in the polymer system, which helps to improve the subsequent dispersion uniformity of the carbon nanotubes in the spinning solution, thereby comprehensively improving the conductive uniformity, tensile strength and air permeability of the film.

[0103] As shown in Table 2, by comparing the schemes of Examples 1 and 4, it can be seen that compared with Example 4, in Example 1, the carbon nanotubes are pre-treated with high-temperature calcination, which helps to change their surface properties during the high-temperature calcination process, so that the carbon nanotubes have more microholes and pores. When the carbon nanotubes are subsequently surface treated with hexadecyltrimethylammonium bromide, the adsorption efficiency of the carbon nanotubes on hexadecyltrimethylammonium bromide can be improved, and the dispersion uniformity of the carbon nanotubes in the spinning solution can be promoted, so that the conductive uniformity of the film is further improved.

[0104] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a conductive masterbatch, characterized in that: The following steps are involved: The carbon nanotubes are calcined in an inert gas atmosphere at a temperature greater than or equal to 600° C. and less than or equal to 900° C., and then added into an organic solvent containing hexadecyltrimethylammonium bromide to obtain a mixed solution, heated and stirred, filtered, and dried to obtain modified carbon nanotubes. 62wt%-73wt% of polymer melt A, 1-3wt%wt% of coupling agent and 25wt%-35wt%wt% of the modified carbon nanotubes are mixed, melted and extruded to obtain conductive masterbatch.

2. The method for preparing a conductive masterbatch according to claim 1, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide to the carbon nanotubes in the mixed solution is greater than or equal to 2 and less than or equal to 4, and the mass fraction of the hexadecyltrimethylammonium bromide in the organic solvent containing hexadecyltrimethylammonium bromide is greater than or equal to 30wt% and less than or equal to 40wt%.

3. The method for preparing a conductive masterbatch according to claim 1, characterized in that: The carbon nanotube calcination time is greater than or equal to 1 hour and less than or equal to 5 hours, the heating temperature of the mixed solution is greater than or equal to 50° C. and less than or equal to 80° C., and the melt granulation temperature is set to be greater than or equal to 160° C. and less than or equal to 210° C.

4. The method for preparing a conductive masterbatch according to claim 1, characterized in that: The polymer melt A is at least one of polyesters such as polyethylene, high-density polyethylene, polypropylene, polybutene, polymethylpentene, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, PET, and polylactic acid; the coupling agent is at least one of a silane coupling agent, a titanate coupling agent, and a phosphate coupling agent; the length of the carbon nanotube is greater than or equal to 1 μm and less than or equal to 50 μm, and the diameter is greater than or equal to 5 nm and less than or equal to 100 nm.

5. A conductive masterbatch prepared by the method for preparing a conductive masterbatch according to any one of claims 1 to 4.

6. A method for preparing a polyolefin conductive film by a flash evaporation method, characterized in that: Using a conductive masterbatch as claimed in claim 5, comprising the following steps: The polymer melt B, the conductive masterbatch and the spinning solvent are mixed in a reaction kettle, heated to a temperature greater than or equal to 190° C. and less than or equal to 230° C., pressurized to a temperature greater than or equal to 10 MPa and less than or equal to 12 MPa, and stirred in a closed manner until the temperature and pressure are stable to obtain a spinning solution, wherein the spinning solution includes 8wt%-13wt% of the polymer melt, 7wt%-10wt% of the conductive masterbatch and 77wt%-85wt% of the spinning solvent in a mass fraction, The spinning solution is ejected through the spinneret holes of the connected flash spinning device, stretched and opened by an air amplifier to form an ultrafine fiber web, and then laid on a mobile device, and subjected to cold pressing and hot rolling to obtain a film.

7. The method for preparing a polyolefin conductive film by flash evaporation as claimed in claim 6, characterized in that: The polymer melt B is at least one of polyesters such as polyethylene, high-density polyethylene, polypropylene, polybutene, polymethylpentene, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, PET, and polylactic acid, and the spinning solvent is at least one of toluene, benzene, n-hexane, butane, pentene, heptane, octane, cyclohexane, cyclopentane, dichloromethane, carbon tetrachloride, chloroform, chloromethane, ethyl chloride, dichloroethylene, trichlorofluoromethane, dichlorotrifluoroethane, pentafluoropropane, heptafluoropropane, perfluorohexane, perfluorohexane, perfluoroheptane, octafluorocyclopentane, and alcohol solvents.

8. The method for preparing a polyolefin conductive film by flash evaporation as claimed in claim 6, characterized in that: Satisfy at least one of the following a)-d): a) the spinning solution is stirred in the reactor in a closed state for a period of time greater than or equal to 2 hours and less than or equal to 5 hours, b) the air flow rate of the spinneret of the flash spinning device is greater than or equal to 10000 m / min and less than or equal to 13000 m / min, and the diameter of the spinneret is greater than or equal to 1 μm and less than or equal to 5 μm, c) the cold pressing pressure is greater than or equal to 0.5 MPa and less than or equal to 2 MPa, d) The hot rolling temperature is greater than or equal to 120° C. and less than or equal to 140° C., and the pressure is greater than or equal to 3 MPa and less than or equal to 4 MPa.

9. A flash evaporated polyolefin conductive film prepared by the method for preparing a flash evaporated polyolefin conductive film as claimed in any one of claims 6 to 8.

10. Use of the flash evaporated polyolefin conductive film as claimed in claim 9 in the field of preparing conductive materials or membrane electrode gas diffusion layers.